The Use of Viscoelastic Material to Damp Vibration in Buildings and Large Structures - Nelson, Frederick C. (Engineering Journal, 1968)
Controlling the vibration response of structures is a problem which has received the attention of many engineers for many years. This paper discusses some recent developments of a special aspect of this general problem; namely the use of viscoelastic material to damp the low frequency vibration often associated with large scale structures and buildings. The growing concern of structural engineers with the airborne and structure borne vibration environment of their buildings is a reflection of the growing concern of the engineering profession, as well as the general public, with the problem of noise and vibration. Economic considerations and improved design methods have resulted in a trend to lighter weight structures and higher speed machinery, both of which tend to increase vibration levels. The engineer must either develop new methods of controlling vibration or adapt or improve existing methods if the public good is to be served. As an example of adaptation, this paper describes three cases in which constrained viscoelastic layers, first employed in the aerospace industry, have been used to control the vibration of large structures.